Courts and Trials : A Multidisciplinary Approach - Friedland, Martin L. (Book collections on Project MUSE., 1975)
The judicial system occupies an important place in society, yet it has been one of the least studied of Canadian institutions, traditionally left to lawyers and members of the legal profession. In this volume nine non-lawyers scrutinize its operation in Canada from the perspectives of several academic disciplines.